Exploring Verbal Relations between Arden of Faversham and John Lyly’s Endymion - Freebury-Jones, Darren (Renaissance and Reformation / Renaissance et Réforme, 2018)
Several scholars, utilizing traditional reading-based methods, have highlighted intertextual links between the anonymous domestic tragedy Arden of Faversham (1590) and John Lyly’s comedy Endymion, The Man in the Moon (1588). The authorship of Arden of Faversham is fiercely contested: Brian Vickers and the present writer have argued for Thomas Kyd’s sole authorship, whereas MacDonald P. Jackson and his New Oxford Shakespeare colleagues have contended for Shakespeare’s part authorship. This article draws upon electronic corpora in order to highlight matching utterances between the Kentish tragedy and Lyly’s comedy, and suggests that the quantity of rare and/or unique verbal parallels with Endymion is indicative of a single author’s acquisitive practices. The article proceeds to explore these matches in context in order to broaden our understanding of the relations between these plays, and the composition of Arden of Faversham as a whole.